Development and Characterization of Nickel Free Duplex Stainless Steel - Kumar, Alok (My University, 2008)
A new high nitrogen, Ni free duplex stainless steel containing 21wt% Cr, 1.6wt% Cu, 5wt% Mn, 0.2wt% N has been developed. This stainless steel was tested for its mechanical and corrosion behavior in several organic acids, inorganic acids and salts. Result shows that this stainless steel with 58% ferrite has much higher yield strength and corrosion resistance compared to standard austenitic stainless steels: 304, 304L and 316L. This stainless steel also exhibited superior corrosion resistance compared to 304N, 316N and duplex ( low Ni) stainless steel containing similar chromium and manganese with 1.5wt% nickel content. The newly developed duplex (Ni free) stainless steel has better corrosion resistance property in sulfuric acid media and in other inorganic media. This duplex stainless steel also behaves better in organic media and craft solutions. This duplex stainless steel can be used in chemical industry, pulp and paper industry, where high strength and good corrosion resistance property are required.
M.Tech, SPMS
Keywords: Duplex; Stainless; Ni free